Oral Lipid Based Formulation: A Review - M. NAGARAJU PATRO,; AJIT S. BANKAR,; SACHIN UTTAM RAKESH,; DR. A. V. YADAV, (International Journal of Pharma and Bio Sciences, 2010)
Lipid and surfactant based formulations are exclusively used for poorly aqueous soluble drugs. Lipid based formulations (LBF) include solid, liquid and semi-solid dispersion. These are generally formulated as self emulsifying, non-emulsifying, micro emulsifying drug delivery systems. Lipid excipients are generally obtained from natural sources also can be synthesized chemically. This review summarizes the use of lipid excipients, formulation methods and characterization of lipid based formulations of poorly aqueous soluble drugs. Special attention has been paid to the lipid excipient classes, with special emphasis on their characterization, and various techniques adopted for preparation of liquid, solid and semi- solid lipid formulations.